Proposed Problem-Solving Method and Implementation at PT. SKJ - Cheryl Marlitta Stefia; Heru Kristanto (Ridwan Institute, 2022)
SKJ faces several problems related to human capital and there is a mismatch between the work standards set by the company and the objectives that must be achieved. The focus for this case is primarily internal and sometimes influenced by external circumstances (ex: competitors). Current human resources have different skills and are generally unable to do other jobs. This condition occurs in the production section, where workers in the company are required to be able to use not just one tool but all of them. For example, the dough cutting section must understand how to use a seasoning machine. Therefore, this study aims to present a Proposed Problem-Solving Method and Implementation at PT. SKJ to maximize the potential of PT. SKJ in the future. Using fishbone analysis, the Marketing model presented by McKinsey is more familiarly called 7S and schedule management helps to provide the following solutions: (1) prioritize the process of planning, implementing, and evaluating policies in an accurate and periodically determined manner so that they are more organized for all layers including from the perspective of the owner and employees, (2) optimizing human resources by instilling the company's vision and mission for character building for those involved in the company, (3) provide apparent problem solving for work time and payroll processes in order to be profitable and will not cause confuse, and (4) providing a good understanding of the product and encouraging employees to provide input regarding product innovation based on market conditions and existing competitors.